2015
DOI: 10.1039/c5ob01044f
|View full text |Cite|
|
Sign up to set email alerts
|

Total synthesis of two potent anti-inflammatory macrolactones of the oxacyclododecindione type

Abstract: An esterification/Friedel-Crafts-cyclization approach permitted the first successful synthetic entry into the oxacyclododecindione subclass of the dihydroxyphenylacetic acid lactone-type natural products. This route allowed the preparation of two highly active anti-inflammatory fungal secondary metabolites 14-deoxyoxacyclododecindione and 14-deoxy-4-dechlorooxacyclododecindione as well as their 14-desmethyl analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…3,4,10−12 To date, two natural products and 10 synthetic derivatives of the oxacyclododecindione series have been successfully synthesized. 5,9 All of the retrosynthetic approaches followed a strategy based on the key step of an intramolecular Friedel-Crafts acylation (IFCA) at low substrate concentration and low temperature. 5,9,11 Other approaches to the ring closure of the 12-membered lactone, such as carbonylative cross-coupling, hydroacylation, or metathesis reaction, have not proved fruitful.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,10−12 To date, two natural products and 10 synthetic derivatives of the oxacyclododecindione series have been successfully synthesized. 5,9 All of the retrosynthetic approaches followed a strategy based on the key step of an intramolecular Friedel-Crafts acylation (IFCA) at low substrate concentration and low temperature. 5,9,11 Other approaches to the ring closure of the 12-membered lactone, such as carbonylative cross-coupling, hydroacylation, or metathesis reaction, have not proved fruitful.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5,9 All of the retrosynthetic approaches followed a strategy based on the key step of an intramolecular Friedel-Crafts acylation (IFCA) at low substrate concentration and low temperature. 5,9,11 Other approaches to the ring closure of the 12-membered lactone, such as carbonylative cross-coupling, hydroacylation, or metathesis reaction, have not proved fruitful. 7 The synthesis of 13-hydroxy-14-deoxyoxacyclododecindione (4) commenced with the preparation of the three building esterification and Wittig olefination, followed by the key IFCA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In our previous report on the racemic total synthesis of 4-dechloro-14-deoxyoxacyclododecindione ((±)-3) and 14-deoxyoxacyclododecindione ((±)-4), we found that synthetic (±)-4 was more active on a IL-4/Stat6-dependent and a TGF-β/Smad2/3dependent transcriptional luciferase reporter in transiently transfected HepG2 cells, than the isolated natural product (+)-4. 12,13 There are two possibilities to explain this result; the isolated material had a lower degree of purity, or the unnatural enantiomer (−)-4 is more active than the naturally occurring enantiomer (+)-4. To investigate this issue and to elucidate the absolute configuration of 14-deoxyoxacyclododecindione ((+)-4), a separation of racemic (±)-4 by chiral, preparative HPLC was performed.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the relative configuration of the two adjacent stereocenters was assigned as (14R*,15S*) by racemic total synthesis of 4-dechloro-14-deoxyoxacyclododecindione (3) and 14-deoxyoxacyclododecindione (4). 12,13 Due to their structural analogy to the macrolactones 1 and 2 the absolute configuration was assumed to be (14R,15S). [12][13][14][15] While (−)-1 and (−)-2 show biological activities in the micromolar range, the secondary metabolites 3-5 exhibit anti-inflammatory and anti-fibrotic activities in cell culture experiments at nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation